Match each chemical equation below with the correct equilibrium constant expression.
Chemical Equation Equilibrium Constant Expression
2NO(g) ⇌ N2(g) + O2(g) K =
N2(g) + O2(g) ⇌ N2O2(g) K =
2NO2(g) ⇌ N2(g) + 2O2(g) K =
N2(g) + 2O2(g) ⇌ 2NO2(g) K =
N2(g) + O2(g) ⇌ 2NO2(g) K =
N2O2(g) ⇌ N2(g) + O2(g) K =
Frequently Asked Questions
What scientific concept do you need to know in order to solve this problem?
Our tutors have indicated that to solve this problem you will need to apply the Equilibrium Expressions concept. If you need more Equilibrium Expressions practice, you can also practice Equilibrium Expressions practice problems.